Dysphagia Improvement Following Sublingual Nifedipine Administration in Long-Segment Esophageal Stricture: A Case Report - Steven Jonathan; I Putu Bayu Triguna; Gde Giri Prathiwindya; I Made Suma Wirawan (CV. Inara, 2026)
Dysphagia is a difficulty in swallowing either solid food or liquid. Esophageal stricture being one of the most common causes of dysphagia can be caused by inflammation, fibrosis, or neoplasia damaging the esophageal lumen. If left untreated, dysphagia can lead to malnutrition, aspiration, and decreased quality of life. Another common cause of dysphagia is esophageal motility disorder, an impairment in peristalsis of the esophageal. Calcium channel blockers such as nifedipine have been reported to improve dysphagia and may serve as alternative therapy while waiting for endoscopic intervention. A 27-year-old man presented with a two-month history of progressive dysphagia to solids, semisolids, and liquids, after an episode of hematemesis. Esophagogram showed esophageal stricture with impaired peristaltic. Contrast-enhanced CT result was suggestive of an intraluminal esophageal stricture. The patient was given sublingual nifedipine before meals as an alternative therapy while waiting for endoscopic intervention, and showed gradual sympomatic improvement. Dysphagia caused by long-segment esophageal stricture can be exacerbated by secondary motility disorder. While definitive treatment requires endoscopic intervention, sublingual nifedipine offered effective short-term symptomatic relief by reducing esophagogastric junction pressure and improving bolus transit through the narrowed lumen.